Smart irrigation system using PLC, SCADA, and fuzzy control - Morsi, Iman; Ahmed, Maged (Edelweiss Applied Science and Technology, 2024)
This paper describes the design of smart irrigation control system for a 20-acre farm in Alexandria, Egypt, based on a Graphical User Interface GUI, Supervisory Control and Data Acquisition systems SCADA, Programmable Logic Control PLC, Fuzzy Logic Control FLC, and sensors. A SCADA system with a local Human Machine Interface HMI screen, and remote control through a VPN connection is applied to monitor and regulate the field sensors. There are various agricultural crops on this farm which are affected by the environmental parameters. The measured input parameters are soil moisture, wind speed, pressure, temperature, humidity, rain fall, and soil conductivity. The measured data are extracted from the sensors. The output is then carried out based on the applied PLC, SCADA, and fuzzy control which are designed and implemented to make a decision about the suitable operational irrigation pumps can be used. The comparison between the total daily power consumption per day for the traditional irrigation system which is 352 KWh/day, and the total daily power consumption per day for the smart control irrigation system which is 242 KWh/day, resulting the reduction rate in power and cost is 31.25%. PLC, SCADA, and fuzzy control ensure long-term water conservation in agriculture and reduction in the power consumption.